Brand mergers: How attitudes influence consumer identity preferences - César - Machado, Joana (2013)
In the context of a merger, management of corporate brand names and logos assumes a critical role. The purpose of this paper is to provide a better understanding of the corporate brand redeployment decision. This study analyses how consumers’ attitudes towards the corporate brands influence their preferences regarding the different branding strategies. Results suggest that the preference for a monolithic alternative is only clearly supported when one of the partners in the merger is a weak partner. When the merger involves two familiar brands, there is a tendency among consumers to combine elements of both brands’ identity. Finally, it is concluded that the affective and behavioural dimension of attitude towards the brand have a significant influence on consumers’ preferences.